(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. Evoluzione storica del lettorato: da ordine minore a ministero istituito - 3. Normativa canonica universale sul ministero del lettorato: dal CIC del 1983 a oggi - 4. Il diritto particolare della Conferenza episcopale italiana sul ministero del lettore: dal 1973 a oggi - 5. Discussione sull’accesso della donna al ministero del lettorato - 6. Conclusioni. The ministry of lector: historical-canonical perspectives and Italian Episcopal Conference particular law ABSTRACT: The paper intends to analyze the ministry of lector, describing its historical evolution from the minor order to institued ministry, after the motu proprio Ministeria quaedam of Pope Paul VI (1972). Then, the autor proposes an overview of its status in Canon and liturgical laws. Next, the particular law of the Italian Episcopal Conference is analyzed, and, finally, the possibility of the opening of the ministry of lector for women is discussed.